The link between forest, water and people: an agenda to promote in the context of climate change in Central Africa - Sonwa, D.J.; Gapia, M; Pokam, W.M; Losembe, F; Mfochivé, O.F. (2012)
Central Africa is known for its substantial reserve of clean water. This reserve is unfortunately declining with climate changes. While forests, another natural resource of the zone has up to now been the focus of most efforts, mainly for biodiversity conservation, this is not yet the case for water resources on which plants are however dependent. In the context of this paper, we revisit (1) climate changes, (2), their impact on the water system, (3) the incidence of disturbances on the water system, (4) the current responses and the way these responses should be oriented for a good synergy between the water, forestry and development sectors in a context of adaptation to climate change.